Aerobic exercise and MOTS-c attenuate diabetic myocardial fibrosis via inhibition of the THBS1/TGF-β signaling pathway - Li, Zhiyu; Wang, Tutu; Fu, Yu; Chen, Feilong; Li, Shunchang (Frontiers in Endocrinology, 2026)
Myocardial fibrosis stands as a defining pathological characteristic in type 2 diabetes. Aerobic exercise curbs the overproduction of type I/III collagen and boosts matrix metalloproteinases, thereby improving outcomes related to fibrosis in the heart. Although physical activity is well known for its positive effects on cardiac well-being in diabetic individuals, sticking to an exercise regimen proves to be a tough nut to crack for many patients. The mitochondrial peptide MOTS-c could serve as a stand-in for exercise, delivering cardioprotective benefits akin to those from working out. This study delved into the molecular mechanisms behind how exercise and MOTS-c influence cardiac fibrosis in diabetes. Both approaches led to marked enhancements in glucose and lipid metabolism, lowered collagen buildup, and bettered both systolic and diastolic heart functions. Through transcriptomic profiling, THBS1 emerged as a pivotal gene that was altered, with reduced activity in the THBS1/TGF-β pathway verified at mRNA and protein stages. In a nutshell, these insights indicate that aerobic exercise and MOTS-c alleviate myocardial fibrosis in diabetes, most likely by putting a damper on the THBS1/TGF-β signaling pathway. These findings establish a theoretical foundation for treating diabetic myocardial fibrosis.